Encontre o valor de f(3)+f(-1) quando a função seguir a lei f(x)=4x+1
Soluções para a tarefa
Respondido por
1
f(x)=4x+1
f(3)= 4.3+1
f(3)= 12+1
f(3)= 13
f(-1)= 4.(-1)+1
f(-1)= -4+1
f(-1)= -3
f(3)-f(-1)=13-3=10
f(3)= 4.3+1
f(3)= 12+1
f(3)= 13
f(-1)= 4.(-1)+1
f(-1)= -4+1
f(-1)= -3
f(3)-f(-1)=13-3=10
Respondido por
0
f(x)= 4.3+1+1
f(x)= 12+2
f(x)= 14
f(x)= 12+2
f(x)= 14
Perguntas interessantes
Geografia,
11 meses atrás
Matemática,
11 meses atrás
Português,
11 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás